1983
DOI: 10.1063/1.93861
|View full text |Cite
|
Sign up to set email alerts
|

Photovoltaic properties of cadmium sulfide/trivalent-metal phthalocyanine heterojunction devices

Abstract: Thin-film photovoltaic devices consisting of a CdS/trivalent-metal phthalocyanine heterojunction have been prepared. The devices are fabricated by first electrodepositing a thin film of CdS onto a transparent conducting indium-tin-oxide substrate and then depositing phthalocyanine and gold layers sequentially in a vacuum coater. The trivalent-metal phthalocyanines used are chloroaluminium chlorophthalocyanine (ClAlClPc), chloroaluminium phthalocyanine (ClAlPc), and chloroindium phthalocyanine (ClInPc). Under a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

1985
1985
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 9 publications
0
17
0
1
Order By: Relevance
“…Under an A M 2 illumination of 7 5 m W ~m -~, conversion efficiencies of 0.22% were measured for the most performing Pcs: ClAlPc and ClAlClPc (7). Unlike the case of n-CdS/p-Cu2S, where the space charge region is situated in the CdS layer, it has been demonstrated that for a n heterojunction with a phthalocyanine (5,8), the space charge region is located exclusively in the organic semiconductor film.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Under an A M 2 illumination of 7 5 m W ~m -~, conversion efficiencies of 0.22% were measured for the most performing Pcs: ClAlPc and ClAlClPc (7). Unlike the case of n-CdS/p-Cu2S, where the space charge region is situated in the CdS layer, it has been demonstrated that for a n heterojunction with a phthalocyanine (5,8), the space charge region is located exclusively in the organic semiconductor film.…”
Section: Introductionmentioning
confidence: 94%
“…Later on, following the example of inorganic cells like n-CdS/p-Cu2S, photovoltaic devices of the type n-CdS/p-PC were developed (5)(6)(7)(8)(9). Under an A M 2 illumination of 7 5 m W ~m -~, conversion efficiencies of 0.22% were measured for the most performing Pcs: ClAlPc and ClAlClPc (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The powder was heated in aqueous ammonia solution (30%) in the presence of pyridine for 12 h to give PcAlOH. The product was then washed by repeated solvent extraction techniques with acetone, ethanol, and chloroform (14).…”
Section: Methodsmentioning
confidence: 99%
“…As ftalocianinas podem ser usadas como parte integrante da camada geradora de cargas e estão, normalmente, dispersas em uma faixa polimérica. Os tipos de ftalocianinas consideradas para este tipo de aplicação são: ftalocianinas base livre [13,14,15]; ftalocianinas de metais trivalentes, tais como a cloro-alumínio-ftalocianina (ClAlPc) [16] e cloro-índio-ftalocianina (ClInPc) [17,18]; as ftalocianinas dos metais tetravalentes tais como a vanidil ftalocianina (VOPc) [19] e titanil ftalocianina (TiOPc) [20].…”
Section: Capítulo I I-1 Introduçãounclassified